2014
DOI: 10.1167/tvst.3.4.5
|View full text |Cite
|
Sign up to set email alerts
|

Depth Resolved Differences After Corneal Crosslinking With and Without Epithelial Debridement Using Multimodal Imaging

Abstract: Citation: Gupta P, Anyama B, Edward K. Depth resolved differences after corneal crosslinking with and without epithelial debridement using multimodal imaging. Tran Vis Sci Tech. 2014;3(4):5, http://tvstjournal. org/doi/full/10. 1167/tvst.3.4.5, doi: 10.1167/tvst.3.4.5 Purpose: To quantitatively compare stromal collagen architecture and keratocyte viability between two methods of corneal crosslinking (CXL), one involving invasive epithelial debridement (standard riboflavin crosslinking) and the other by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 31 publications
1
7
0
Order By: Relevance
“…Quantitative tools such as the FFT [26, 29, 31] or a roughness score [27] have been shown to be useful procedures to detect changes in porcine corneal stroma after CXL treatment in both forward and backward SHG images. Similar to the results here obtained, the later configuration reported that standard CXL produced significant architectural changes of the deeper stroma.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Quantitative tools such as the FFT [26, 29, 31] or a roughness score [27] have been shown to be useful procedures to detect changes in porcine corneal stroma after CXL treatment in both forward and backward SHG images. Similar to the results here obtained, the later configuration reported that standard CXL produced significant architectural changes of the deeper stroma.…”
Section: Discussionmentioning
confidence: 99%
“…In porcine corneas, forward SHG images showed that linear collagen fibers of control samples became wavy after CXL treatment [26]. In backward SHG images, treated porcine corneas presented an attenuated rugged/wavy pattern compared to the control group [27]. In a similar experiment (although comparisons with an accelerated CXL procedure were also made), CXL specimens were reported to present an increased fibrillar contrast in comparison with untreated baseline SHG images [28].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations